E-Safe Sdn. Bhd / Erzura Najwa Othman … [et al.] - Othman, Erzura Najwa; Abdul Rashid, Shareeda; Zulkipli, Nor Wahidah; Suhaimi, Mohd Fairuz; Mohd Hamdan, Siti Khadijah (2004)
Name of company E-SAFE SDN BHD Nature of business > Manufacturer and supplier of fire fighting equipment Industry profile > Competitive > High demand in market > For safety > High potential to export > Future expectation - upgraded product of fire fighting equipment Location Lot 878, Jalan Subang 9, Taman Perindustrian Subang, 47500 Subang jaya, Selangor Darul Ehsan, Malaysia. Date of business commencement 14 February 2006 Factor in selecting the propose business > Increasing demand in safety product > Increasing consumer consent about safety Future prospect of business > In the future, we aspect the increasing of consumer consent about Safety 8 > In the future, we also aspect to decreasing a fatal-causing and ending of death or disaster because of fire